Fundamental basis for distance relaying with parametrical estimation. - Segui, T. (IEEE Transactions on power delivery)
This paper deals with the application of parametrical estimation to transmission line protection. A classification of several algorithms based on the line differential equation, is described. New algorithms are proposed and evaluated with transient simulations